1983
DOI: 10.1099/00221287-129-3-801
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Replication and Incompatibility Genes of an IncFVI Haemolysin Plasmid with Other F-like Haemolysin Plasmids

Abstract: The replication and incompatibility region of the IncFVI plasmid pSU502 has been isolated by in vitro DNA manipulation as part of a 12.6 kb plasmid, denominated pSU503. Plasmid pSU503 was strongly incompatible with its parental plasmid, pSU1, but was fully compatible with the haemolytic plasmids pSU3 16 (IncFIII/IV), pHly152 (IncI2) and pSU233 (Inc-pSU233). Furthermore, the 6.9 kb EcoRI fragment of pSU503 which carries the replication and incompatibility determinants of pSUl did not show any detectable homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…The results, shown in Table 1, indicated that (i) the 0.8 kb fragment contains an incompatibility determinant; (ii) this incompatibility determinant is able to suppress the replication of the miniplasmid pSU325 1, which strongly suggests that pSU325 1 is replicated from the RepFVIB replicon; and (iii) the fragment does not inhibit the replication of the parental plasmid pSU401. This last result was consistent with that of Zabala et al (1983) and indicated the presence of more than one functional replicon in pSU401. In addition, pSU3252 showed partial incompatibility towards the IncFVII miniplasmid pSU3201.…”
Section: Isolation Of An Incf VI Incompatibility Determinantsupporting
confidence: 90%
“…The results, shown in Table 1, indicated that (i) the 0.8 kb fragment contains an incompatibility determinant; (ii) this incompatibility determinant is able to suppress the replication of the miniplasmid pSU325 1, which strongly suggests that pSU325 1 is replicated from the RepFVIB replicon; and (iii) the fragment does not inhibit the replication of the parental plasmid pSU401. This last result was consistent with that of Zabala et al (1983) and indicated the presence of more than one functional replicon in pSU401. In addition, pSU3252 showed partial incompatibility towards the IncFVII miniplasmid pSU3201.…”
Section: Isolation Of An Incf VI Incompatibility Determinantsupporting
confidence: 90%